2011
DOI: 10.1002/nbm.1698
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of tumor‐associated macrophages during tumor expansion using MRI

Abstract: MRI is being used increasingly for the noninvasive longitudinal monitoring of cellular processes in various pathophysiological conditions. Macrophages are the main stromal cells in neoplasms and have been suggested to be the major cell type ingesting superparamagnetic iron oxide (SPIO) nanoparticles. However, no MRI study has described longitudinally the presence of tumor-associated macrophages (TAMs) during tumorigenesis with histological confirmation. To address this, we injected SPIO nanoparticles into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 52 publications
3
23
0
Order By: Relevance
“…It has been demonstrated that the recruitment of these cells into the tumor microenvironment is crucial for de novo vessel formation and angiogenic switch (43). Consistent with this idea, we also observed early stepwise deposits of myeloid cells close to the vessel lumen (44), and the timeline of deposition matches the timeline of the multiple high K trans peaks developing from day 7 to day 14 ( Fig. 1).…”
Section: Discussionsupporting
confidence: 88%
“…It has been demonstrated that the recruitment of these cells into the tumor microenvironment is crucial for de novo vessel formation and angiogenic switch (43). Consistent with this idea, we also observed early stepwise deposits of myeloid cells close to the vessel lumen (44), and the timeline of deposition matches the timeline of the multiple high K trans peaks developing from day 7 to day 14 ( Fig. 1).…”
Section: Discussionsupporting
confidence: 88%
“…A mix of microscopic (cellular resolution) and whole-animal imaging methods were used to investigate the distribution of the reagent, 41 , 42 the route of accumulation at the tumor site, 43 and examples of the complex interplay between host and tumor cells 44 , 45 . The optical imaging of an unrelated, integrin-targeting PFC-NIR formulation has previously been used to study tumor vasculature 46 .…”
Section: Discussionmentioning
confidence: 99%
“…In-vivo labeling of monocytes/macrophages with iron-oxide particles for MRI has been applied to image many disease conditions, such as graft rejection, atherosclerotic plaques, tumors, abdominal aortic aneurysm, renal ischemia, and Alzheimer’s disease [2,10,25,27,28,29,30,31,32,33]. Our laboratory has been able to monitor the infiltration of macrophages labeled with USPIO or MPIO particles at rejecting kidneys, hearts, and lungs in our rat models for organ transplantation using the in-vivo labeling procedure [2,10,25,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive in-vivo MRI of monocytes/macrophages labeled with iron-oxide particles may lead to a better understanding of the pathogenesis of many diseases, including graft rejection [2,10,25,26], atherosclerotic plaques [27,28], tumors [29,30], abdominal aortic aneurysm [31], renal ischemia [32], Alzheimer’s disease [33], etc. Due to the fact that monocytes/macrophages are phagocytes, they can be labeled in vivo by a direct injection of suitable iron-oxide particles.…”
Section: Introductionmentioning
confidence: 99%